The history of the spread of islam in india and its relationship with islam in the archipelago: a critical review - Thosimah; Fathul Khair; Suyono Umar; Jundil Islam Muhammad Muslikhin (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
This study describes the history of the spread of Islam in India and its relationship with the Archipelago. This study uses historical methods and a sociological approach. This research is a library research with a research focus, namely how is the history of the arrival of Islam in the Indian region? and How is the relationship between Indian Islam and Nusantara Islam? The results of this research are that the early history of the entry of Indian Islam is divided into two, namely formal and non-formal. The formal spread of Islam, namely the spread during the time of the Prophet, at that time many Jat (Indian) tribes lived in Arabia and some became physicians who healed the illness of Aisha, the wife of the Prophet, who was eventually appointed as his khadimah. The spread in the Rashidun khulafaur era at the time of Umar bin Khatab who carried out the expansion which was then continued by the next government until the Umayyads and the dynasties after it such as the Ghazni dynasty, Ghuri, the Delhi sultanate, the Khalji dynasty, Tughlaq, Sayyid, and finally the Mughal dynasty. non-formal, namely by trade, figures of Alim Ulama and marriage. Meanwhile, the relationship between India and the Archipelago occurred because of trade routes which later led to the entry of Islam. The strongest theory of Islamization in the archipelago was carried out by traders from Gujarat. This theory is believed from the many historical evidences, one of which is the legacy of Malik al Saleh who came from Bangala